Gender-Specific Differences in Presentation and Management of Spinal Infection: A Single-Center Retrospective Study of 159 Cases. Issue 4 (May 2021) - Lener, Sara; Wipplinger, Christoph; Hartmann, Sebastian; Rietzler, Andreas; Thomé, Claudius; Tschugg, Anja
Study Design: A retrospective single-center analysis of 159 cases. Objective: To investigate differences between male and female patients, as spinal infection (SI) represents a life-threatening condition and numerous factors may facilitate the course and outcome of SI, including patients' age and comorbidities, as well as gender. To date, no comparative data investigating sex differences in SI is available. Thus, the purpose of the present retrospective trial was to investigate differences between male and female patients. Methods: A total of 159 patients who were treated for a spinal infection between 2010 and 2016 at our department were included in the analysis. The patients were categorized into 2 groups based on gender. Evaluation included magnetic resonance imaging, laboratory values, clinical outcome, and conservative/operative management. Results: Male patients suffered from SI significantly more often than female patients (n = 101, 63.5% vs n = 58, 36.5%, P = .001). However, female patients were initially affected more severely, as infection parameters were significantly higher ( P = .032) and vertebral destruction was more serious ( P = .018). Furthermore, women suffered from intraoperative complications more often ( P = .024) and received erythrocyte concentrates more frequently ( P = .01). Nevertheless, mortality rates and outcome were comparable. Pain scales were significantly higher in female patients at 12-month follow-up ( P = .042). Conclusion: Although male patients show a higher incidence for SI, the course of disease and the management is more challenging in female patients. Nevertheless, outcome after 12 months is comparably good. Underlying mechanisms may include a better immune response and dissimilar effects of antibiotic treatment in women. Pain management in female patients is still unsatisfactory after 12 months.